Pulmonary Empty Spaces: Silicone Embolism—A Decade of Increased Incidence and Its Histological Diagnosis - Kirill Lyapichev; Felix Manuel Chinea; Julio Poveda; Jeniffer Pereda; Pablo A. Bejarano; Monica T. Garcia-Buitrago (Case Reports in Pathology)
Pulmonary embolism (PE) is a critical complication related to multiple disorders and different medical or cosmetic procedures. This case report presents two patients who were admitted for respiratory symptoms in the setting of previously receiving silicone injections for cosmetic purposes and were diagnosed with silicone pulmonary embolism. The relevance of including questions about all cosmetic procedures as a part of a medical history is highlighted, in particular about silicone injections. The diagnosis is confirmed by histological means. Additionally, our review showed the change of most common sites of silicone injections and a significant increase in cosmetic procedures causing silicone embolism during the past twelve years.